NYPD red - Patterson, James, 1947- (Little, Brown and Company, 2012)
Detective Zach Jordan investigates a series of brutal, public crimes that coincide with the arrival of dozens of glamorous celebrities in town for parties and premieres. NYPD Red is a special task force charged with protecting the interests of Manhattan's wealthiest and most powerful citizens. When a world-famous movie producer is poisoned on the first day of a Manhattan film festival called Hollywood on the Hudson, they are the first ones called.